Fetuses are not adult humans: a response to Miller on abortion - Saunders, Ben (Journal of medical ethics, 2024)
Miller has recently argued that fetuses have the same inherent value as non-disabled adults. However, we do not need to postulate some property possessed equally by all humans, including fetuses, in order to explain the equality of non-disabled adults. It would suffice if there were some property possessed by all non-disabled adults, but not by fetuses.